2018
DOI: 10.1002/cctc.201800474
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Epoxides and Lactones by Cationic Indium Catalysts To Form Functionalized Spiro‐Orthoesters

Abstract: We prepared ac ationic indium catalyst for the conversion of epoxidesa nd lactones into spiro-orthoesters (SOEs), af amily of expanding monomers. The cationic indium alkyl complexesimino}methyl)phenol, S = OEt 2 or THF) weres ynthesized and fully characterized. The reactiono fe-caprolactonew ith 1,2-epoxy-7-octene resulted in the formation of 2-(hex-5-en-1-yl)-1,4,6-trioxaspiro[4.6]undecane (SOE1)w ith full conversion of both components. We extended the substrate scope to five-and six-membered lactones as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 85 publications
0
27
0
Order By: Relevance
“… 23 In particular, we showed that cationic indium complex (±)-[(NN i O Cm )In(CH 2 SiMe 3 )][B(3,5-(CF 3 ) 2 C 6 H 3 ) 4 ] (Cm = Cumyl) catalyzes the coupling of an equimolar mixture of ε-caprolactone (ε-CL) and 1,2-epoxy-7-octene (EOE) to form 2-(hex-5-en-1-yl)-1,4,6-trioxaspiro[4.6]undecane (SOE1) in near quantitative isolated yield. 24 We showed that 5, 6, and 7-membered lactones as well as epoxides with a range of functionality are converted to the respective spiroorthoesters quantitatively. 24 …”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“… 23 In particular, we showed that cationic indium complex (±)-[(NN i O Cm )In(CH 2 SiMe 3 )][B(3,5-(CF 3 ) 2 C 6 H 3 ) 4 ] (Cm = Cumyl) catalyzes the coupling of an equimolar mixture of ε-caprolactone (ε-CL) and 1,2-epoxy-7-octene (EOE) to form 2-(hex-5-en-1-yl)-1,4,6-trioxaspiro[4.6]undecane (SOE1) in near quantitative isolated yield. 24 We showed that 5, 6, and 7-membered lactones as well as epoxides with a range of functionality are converted to the respective spiroorthoesters quantitatively. 24 …”
Section: Introductionmentioning
confidence: 89%
“… 24 We showed that 5, 6, and 7-membered lactones as well as epoxides with a range of functionality are converted to the respective spiroorthoesters quantitatively. 24 …”
Section: Introductionmentioning
confidence: 89%
“…40 kg/mol with relatively narrow dispersity (Đ < 1.3). [49][50][51] This system also effectively copolymerized ECH with THF, oxetane, oxepane, and lactide to make some interesting copolymers.…”
Section: Cationic Ring Opening Polymerization Of Echmentioning
confidence: 99%
“…Mehrkhodavandi et al prepared a cationic indium-based catalyst for the synthesis of SOEs from lactones and epoxides [ 63 ]. The indium complex catalyzes the reaction of 1:1 mixtures of a variety of epoxides and lactones into SOEs, which were obtained as racemic mixtures of diastereomers.…”
Section: Expanding Oxacyclesmentioning
confidence: 99%